INOVASI, LITERASI DIGITAL, & PENDEKATAN PEMASARAN: UPAYA PENGEMBANGAN KAPASITAS PEREMPUAN PENENUN DI DESA REMBITAN, KABUPATEN LOMBOK TENGAH, NUSA TENGGARA BARAT - Utami, Karina Juniarti; Saksono, Herie (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
This study reveals various interconnected and intertwined practical aspects in the capacity development of women weavers in Rembitan Village, Central Lombok Regency, West Nusa Tenggara Province (NTB). Amid the widespread impact of "Triple Disruptions," significant, dramatic, and massive changes have occurred. Product innovation, digital literacy mastery, and marketing approaches focusing on market access and branding have become the main pillars of collective concentration, particularly in supporting the development of traditional weaving businesses. The participation of 30 female weaving artisans in focused group discussions (FGDs) further reinforced the purpose of this activity: to identify Strengths, Opportunities, Aspirations, and Results (SOAR) to discover innovations for the advancement of the home-based weaving industry. Rembitan Village was selected as the locus of the study. Through SOAR Analysis Technique, several findings were noted as major constraints: access to capital, marketing, product quality, and weaver regeneration, as well as the urgency of innovation in the increasingly rare weaving sector. The interaction among women weavers successfully formulated a more affirmative special access program tailored to their fundamental needs. The expected targets include the establishment of a weaving cooperative, sustainable business skills training, intensified and profitable digital marketing, and an artisan regeneration program. The program implementation is designed with clear stages, encompassing planning, socialization, training execution, and development of a joint marketing platform. Success indicators are established, including targets for income increase and growth in the number of young artisans. Periodic evaluation methods are planned to ensure program sustainability. The capacity development of women weavers in Rembitan Village has fostered innovation, cultivated digital literacy, and facilitated marketing approaches for Lombok's distinctive woven fabric products from Rembitan Village in Central Lombok Regency. These findings provide a foundation for developing more effective, efficient, economical, and contextual empowerment policies and programs in the future. Only through innovation and digital literacy can women weavers become increasingly skilled in optimizing marketing through digital platforms. Moreover, the capacity development of women weavers has built a creative community that serves to strengthen the local economy, preserve invaluable cultural heritage, improve community welfare, and enhance regional competitiveness.